2020
DOI: 10.1136/rmdopen-2019-001149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ustekinumab on spondylitis-associated endpoints in TNFi-naïve active psoriatic arthritis patients with physician-reported spondylitis: pooled results from two phase 3, randomised, controlled trials

Abstract: BackgroundThe interleukin-12/23p40-subunit-inhibitor ustekinumab significantly improved spondylitis-related symptoms through Week 24 in psoriatic arthritis (PsA) patients with peripheral arthritis and physician-reported spondylitis (PA-PRS) in PSUMMIT-1&2. We further evaluated ustekinumab’s effect on spondylitis-related endpoints in PSUMMIT-1&2 tumour necrosis factor-inhibitor (TNFi)-naïve patients with PA-PRS.MethodsPatients with active PsA (≥5 swollen and ≥5 tender joints, C-reactive-protein ≥ 3.0 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 30 publications
0
29
0
3
Order By: Relevance
“…To date, according to the EULAR recommendations [62], if axial disease predominates and presents insufficient response to non-steroidal anti-inflammatory drugs, treatment with TNF inhibitor or IL-17A inhibitor should be considered. Furthermore, IL12/23 inhibitor, such as ustekinumab and IL23 inhibitor, such as risankizumab, did not prove clinical efficacy in axial disease [64][65][66]. Thus, more studies are needed to clarify why a drug that inhibits IL23, which acts upstream from IL17, presents no clear clinical efficacy in axial disease, whilst having a good effect in psoriasis [67].…”
Section: Discussionmentioning
confidence: 99%
“…To date, according to the EULAR recommendations [62], if axial disease predominates and presents insufficient response to non-steroidal anti-inflammatory drugs, treatment with TNF inhibitor or IL-17A inhibitor should be considered. Furthermore, IL12/23 inhibitor, such as ustekinumab and IL23 inhibitor, such as risankizumab, did not prove clinical efficacy in axial disease [64][65][66]. Thus, more studies are needed to clarify why a drug that inhibits IL23, which acts upstream from IL17, presents no clear clinical efficacy in axial disease, whilst having a good effect in psoriasis [67].…”
Section: Discussionmentioning
confidence: 99%
“…Ustekinumab, a human IgG1κ monoclonal antibody that binds to the p40 subunit common to IL-12 and IL-23, was approved for the treatment of PsA in 2013 [ 126 ]. Studies have shown that agents that reduce p19 binding to IL-23R may be used to inhibit IL-23 in inflammation, thus inhibiting the p19/IL-23-associated inflammation axis [ 127 ].…”
Section: Interleukin-23mentioning
confidence: 99%
“…Ustekinumab is a human monoclonal antibody that binds to the p40 subunit that is shared by both IL-12 and IL-23 and inhibits the functions of both IL-12 and IL-23. In three clinical trials in patients with PsA, ustekinumab treatment demonstrated higher improvement of the disease activity [ 99 , 100 , 101 ]. Following these results, ustekinumab received FDA approval for the treatment of PsA in 2013.…”
Section: Il-23/il-17 Axis-targeting Therapiesmentioning
confidence: 99%